2014
DOI: 10.1080/10410236.2014.889555
|View full text |Cite
|
Sign up to set email alerts
|

Talking About End-of-Life Preferences in Marriage: Applying the Theory of Motivated Information Management

Abstract: The theory of motivated information management (TMIM) provides one framework to examine information-seeking behaviors, especially in conversations involving sensitive or difficult information such as preferences for end-of-life (EOL) care. The spouse plays a significant role in decision making surrounding EOL care. Consequently, individuals need information about spouses' EOL preferences in order to ensure carrying out those desires. Our findings support the value of TMIM as a framework to understand factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Although initiating conversations about preparation for death can present with significant challenges, couples who do discuss end of life preferences report less fear and anxiety [21] and greater ability to implement desired care. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Although initiating conversations about preparation for death can present with significant challenges, couples who do discuss end of life preferences report less fear and anxiety [21] and greater ability to implement desired care. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have taken a similar approach, collapsing items intended to tap diverse facets of the efficacy construct into a single index. Rafferty et al (2015) found that communication, target, and coping efficacy formed a second-order model, and therefore treated the variable as “a single entity, efficacy judgments” (p. 414). Similarly, W.…”
Section: Methodsmentioning
confidence: 99%
“…The TMIM explains individuals' decisions to seek or avoid information regarding personally significant issues (W. A. Afifi & Weiner, 2004), and has been used to explain information management relating to challenging, taboo, or sensitive matters such as sexual health (Dillow & Labelle, 2014), organ donation wishes (W. A. , family health histories (FHH; Hovick, 2014), and end-of-life preferences (Rafferty, Cramer, Priddis, & Allen, 2015). In constructing the theory, W. A.…”
Section: The Tmimmentioning
confidence: 99%
See 2 more Smart Citations